2009
DOI: 10.1016/j.foodchem.2009.04.067
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl carbamate in pot still cachaças (Brazilian sugar cane spirits): Influence of distillation and storage conditions

Abstract: a b s t r a c tEthyl carbamate (EC), a known genotoxic carcinogen, was studied in 25 brands of pot still cachaças from 19 distilleries in Paraíba State, Brazil. A concentration range of 55-700 lg/l was found with most brands ($70%) exceeding the international EC limit for spirits (150 lg/l). Brand characteristics (colour, distillation [single or double], and bottle colouration) showed no consistent connection with EC levels. However, when EC levels of yellowish (cask matured) and colourless single-distiled cac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 10 publications
3
37
1
3
Order By: Relevance
“…Desta forma, o carbamato de etila formado pós-destilação deve-se à presença de potenciais precursores nas diversas frações do destilado. 20,21 Entretanto, as diferenças entre as concentrações de uretana nos destilados de coluna e nas frações de alambique, recém-obtidas, são devidas ao processo de destilação per se. Isto ocorre independentemente do processo fermentativo.…”
Section: Resultsunclassified
“…Desta forma, o carbamato de etila formado pós-destilação deve-se à presença de potenciais precursores nas diversas frações do destilado. 20,21 Entretanto, as diferenças entre as concentrações de uretana nos destilados de coluna e nas frações de alambique, recém-obtidas, são devidas ao processo de destilação per se. Isto ocorre independentemente do processo fermentativo.…”
Section: Resultsunclassified
“…Apesar de mencionar que, aparentemente, não foi encontrada associação entre a concentração de CE e a coloração de cachaças (que, segundo os autores, a coloração amarelada da bebida indicaria o armazenamento em barris de madeira) analisadas de diferentes destilarias da Paraíba, Nóbrega et al 21 citam que em 2 das destilarias estudadas a concentração de CE encontrada para a cachaça branca foi maior do que para a cachaça amarelada. Isso mostra que, possivelmente, este contaminante pode ser formado, não somente quando a bebida é mantida estocada em recipientes que não são de madeira, mas também quando há a estocagem da cachaça em barris e toneis de diferentes espécies de madeiras.…”
Section: Fração Da Destilaçãounclassified
“…yoghurt, bread) and alcoholic beverages (e.g. wine, beer, whiskey) [3,5,6], being obtained from the reaction between ethanol and nitrogen-containing compounds (e.g. urea, citrulline, hydrogen cyanide, cyanogenic glycosides, and other N-carbamyl compounds), which has a moderate kinetic formation at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, not all nitrogen-containing compounds show the same kinetics when reacting with ethanol. For example, it has been demonstrated that EC formation from urea (which results from the degradation of arginine by yeasts) increases dramatically with temperature (for example in baking, boil- ing or toasting processes) [3,6,7], and more rapidly than from citrulline [8].…”
Section: Introductionmentioning
confidence: 99%